Pesticidal Activities of Some Schiff Bases Derived from Benzoin, Salicylaldehyde, Aminophenol and 2,4 Dinitrophenyl Hydrazine (Journal of Scientific Research, 2009)
The pesticidal activities of three Schiff bases namely PDH [N- (1 phenyl 2 hydroxy 2 phenyl ethylidine) 2¢4¢ dinitrophenyl hydrazine], PHP [N(1-phenyl 2 hydroxy -2 phenyl ethylidine) 2¢ hydroxy phenyl imine] and HHP [N (2-hydroxy benzylidine) 2¢ hydroxy phenyl imine] derived from benzoin, salicylaldehyde, 2 aminophenol and 2,4 dinitrophenyl hydrazine  were evaluated against Tribolium castaneum. Probit mortality were studied by surface film treatment method at different doses of the compounds. The results showed that the LD50 values as recorded after 24 hours of treatment were 15.1268, 3.0922 and 3.0922 mg /cm2 for PDH, PHP and HHP, respectively as compared with 0.2416 mg/cm2 for a standard pesticide l-cyhalothrin. With Schiff base complexes of cobalt(II), copper(II) and zinc(II), the LD50 values were 1.5206, 14.8576 and 3.2829 mg/cm2   respectively. Better results were obtained when recorded with longer treatment time. These three compounds may, therefore, be considered as potent pesticides. Keywords: Pesticidal activities; Schiff bases; Surface film treatment method. © 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245(Online). All rights reserved. DOI: 10.3329/jsr.v1i3.2585             J. Sci. Res. 1 (3), 641-646 (2009)